Perancangan Prototipe Sistem Perparkiran di Universitas Sebelas Maret dengan Menggunakan Teknologi RFId - Yuniaristanto -; Ardy Denta Utama; Roni Zakaria Raung (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2010)
One of the public facilities that still using conventional method is the parking system of Sebelas Maret University. This system has several weaknesses that are: the transaction data is not recorded; lack of security; uncomfortable for the user; and recording tickets every day that cause inefficient in terms of time, effort and cost. So we will be used RFId technology to overcome these parking system weaknesses. We develop an application software through several steps such as software design, database design, interface design, program verification and system validation. The application software that can be integrated with RFId. This software is created by using Borland Delphi 7 and MySQL database.